2009
DOI: 10.1088/0004-637x/696/2/1441
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Morphology and Dynamics of Poor Groups of Galaxies

Abstract: We investigate the relation between the projected morphology and the velocity dispersion of groups of galaxies using two recently compiled group catalogs, one based on the 2MASS redshift survey (Crook et al. 2007) and the other on the SDSS Data Release 5 galaxy catalog (Tago et al. 2008). We analyse a suitable subsample of groups from each catalog selected such that it minimizes possible systematic effects. We find that the velocity dispersion of groups is strongly correlated with the group projected shape and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…It was found that the fraction of massive early-type galaxies (E/S0) and dwarf elliptical galaxies is higher in a dynamically more evolved system with high velocity dispersion (Trentham & Tully 2002;Tovmassian et al 2004;Tovmassian & Plionis 2009). Especially in the case of the NGC 3992 subgroup, which is the most dynamically evolved Ursa Major cluster subgroup, considering its high frequency of early-type galaxies, morphological transformation to early-type galaxies by interactions and merging between galaxies may have occurred more frequently in the early stages of its dynamical evolution than in the other subgroups.…”
Section: Environmental Effects In a Lower Density Clustermentioning
confidence: 99%
“…It was found that the fraction of massive early-type galaxies (E/S0) and dwarf elliptical galaxies is higher in a dynamically more evolved system with high velocity dispersion (Trentham & Tully 2002;Tovmassian et al 2004;Tovmassian & Plionis 2009). Especially in the case of the NGC 3992 subgroup, which is the most dynamically evolved Ursa Major cluster subgroup, considering its high frequency of early-type galaxies, morphological transformation to early-type galaxies by interactions and merging between galaxies may have occurred more frequently in the early stages of its dynamical evolution than in the other subgroups.…”
Section: Environmental Effects In a Lower Density Clustermentioning
confidence: 99%
“…Thus in studies of groups the proper choice of samples is important. To avoid contamination in their study Tovmassian & Plionis (2009) selected a sample of groups in a narrow richness interval to study the dynamics of poor groups.…”
Section: Problems Of the Sample Creation Of Groupsmentioning
confidence: 99%
“…Fortunately, many samples of groups are homogeneous as stated by authors and tested by other investigators. Tovmassian & Plionis (2009) studied the homogeneity of our SDSS DR5 groups (Paper II) and concluded that the sample is homogeneous with respect to virial properties. Nurmi et al (in preparation) studied N-body simulations of dark matter halos comparing the properties of simulated halos with our volume-limited groups of galaxies.…”
Section: Problems Of the Sample Creation Of Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tovmassian & Plionis 2009, and references therein) suggest that groups in the local universe are a family of cosmic structures presently at various stages of their virialization processes. The morphology-density relation found at high density regimes (Dressler 1980) is at work also at the group scale (Postman & Geller 1984).…”
Section: Irrmentioning
confidence: 99%